Gut-eating bugs : maggots reveal the time of death! - Denega, Danielle (New York : Franklin Watts, 2007)
Can bugs tell the time of death? This book has three case studies that explore how insects found on dead bodies help scientists solve the crime and tell the time of death by studying the insects life cycles. This very energetic book has lots of great illustration and content connections.
Includes bibliographical references and index.
G4
Keywords: Forensic entomology; Death -- Time of; Criminal investigation